Optimizing the Use of Electronic Stamps as Tax Revenue in E-Commerce Businesses Linked to the Stamp Duty Law in Indonesia - Paramudhita, Dr. H. Radea Respati; Sinaga, Prof. Dr. H. Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
The COVID-19 pandemic in Indonesia caused an economic crisis that had an impact on the state revenue sector of stamp duty to decline. This decrease occurred due to a policy from the Government in implementing PPKM in accordance with the Instruction of the Minister of Home Affairs Number 15 of 2021 concerning the Enforcement of Restrictions on Emergency Community Activities for Corona Virus Disease 2019 in the Java and Bali Regions. During the implementation of this PPKM, all transactions turn into electronic transactions. With the transition from direct transactions to electronic transactions, the Government is trying to implement electronic stamp duty. Electronicstamp duty is a stamp used for documents in electronic form. The purpose of the imposition of this electronic stamp duty is as a tax on electronic documents. In addition, the purpose of the imposition of electronic stamp duty can be used as legal evidence in proving civil cases. However, in reality, the imposition of electronic stamp duty on electronic transactions carried out in e- commerce has not been effectively carried out.